Research of the Design and Character Test of Energy-regenerative Electromagnetic Actuator - Peng Hu; Zhang Jinqiu; Zhang Jian; Han Chaoshuai; Wang Hui (Jixie chuandong)
In order to realize the purpose of vibration control and energy-regenerative,take some wheel type vehicle as object,an Electromagnetic actuator（ EA） of gear and rack type is designed,the relative math model is built and the analysis of the influence of inertia force and its character of damping is conducted. For the purpose of verifying whether the EA satisfies the design demands,the principle prototype is machined,and the experiment test of its character of mechanical friction,electromagnetic damping,active force and feedback voltage are conducted. The result indicates that the maximum mechanical friction force is 285 N,which satisfy the demand of design restrict. Under the restrain of rated current,the maximum electromagnetic damping force is about 1 100 N,which means a good damping adjust ability. The maximum active force is close to 1 000 N,a bit less than theoretical value,the maximum feedback voltage is about 80 V,during the optimal energy-regenerative interval of suspension relative velocity of 0. 1 ～ 0. 3 m/s,energy-regenerative power is close to hundred Watt of whole vehicle,which is proved possess good ability of energy-regenerative. The EA satisfy the design demand,and the structure scheme is feasible.